Hyperbolic metrics on universal Teichmüller space and extremal problems - Krushkal, S.L. (Український математичний вісник, 2011)
The paper consists of two parts, both related to complex geometry of the universal Teichm¨uller space. We reprove that all contractible invariant metrics on this space coincide and apply this important fact to solving the general extremal problems for univalent functions with quasiconformal extensions.